Answer:
[tex]x=-1[/tex]
Step-by-step explanation:
[tex]\frac{7}{2}x+\frac{1}{2}x=\frac{1}{2}+\frac{9}{2}x[/tex]
Step 1: Simplify both sides of the equation.
[tex]\frac{7}{2}x+\frac{1}{2}x=\frac{1}{2}+\frac{9}{2}x[/tex]
[tex](\frac{7}{2}x+\frac{1}{2}x)=\frac{9}{2}x+\frac{1}{2}[/tex] (Combine Like Terms)
[tex]4x=\frac{9}{2}x+\frac{1}{2}[/tex]
[tex]4x=\frac{9}{2}x+\frac{1}{2}[/tex]
Step 2: Subtract [tex]\frac{9}{2}x[/tex] from both sides.
[tex]4x-\frac{9}{2}x=\frac{9}{2}x+\frac{1}{2}-\frac{9}{2}x[/tex]
[tex]\frac{-1}{2}x=\frac{1}{2}[/tex]
Step 3: Multiply both sides by [tex](\frac{2}{-1})[/tex].
[tex](\frac{2}{-1})*(\frac{-1}{2}x)=(\frac{2}{-1})*(\frac{1}{2})[/tex]
[tex]x=-1[/tex]
Therefore, [tex]x=-1[/tex] will be your final answer.
Sorry this took very long. I had to calculate all of this.